Scientific Literacy in Science Instruction: Media and Teaching Approach Employed - Airiza Dian; Habiddin, Habiddin; Dasna, I Wayan; Rahayu, Sri (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2023)
Students must receive optimal training in science learning to ensure the development of competitive future generations with scientific literacy. This research can be an illustration or source of innovation for educators related to learning media, learning strategies, and learning models that can be applied to train students' scientific literacy. This article presents a description of media and learning strategies implemented in an effort to train students' science literacy skills. Twenty articles published from 2013 to 2022 were obtained from several Q2-Q3 indexed journals such as Journal of University Teaching and Learning Practice; International Journal of Instruction; Bioscene; Journal of Turkish Science; Journal of Mathematics, Science and Technology Education; Journal of Geoscience Education; Journal of Biological Education, Journal of Education and e-Learning Research; European Journal of Eduaction Research; and Eurasian Journal of Educational Research. The review results show that science literacy is widely practiced in science learning at primary, secondary and tertiary levels. Learning strategies and models that are widely used in scientific literacy-based learning such as inquiry models, POGIL, contextual learning, structured project tasks and others. The learning media that are often used are textbook development, web media, Augmented Reality and others. The learning model with great potential to improve scientific literacy is the inquiry model because it has been widely applied. The most recommended learning media are web media and Augmented Reality (AR).